Mathematics
jhousee
45

Using substitution how do you solve -5x+y=-3 3x-8y=24

+4
(1) Answers
dahlianegroni12

-5x+y=-3. (1) isolate y 1.First isolate a variable.( I isolated y because it was already isolated) 3x-8y=24. (2). 2.Then substitute that into the other equation —————. 3. Then solve for X Sub y=5x-3 into (2). 4. Then substitute X into one of the equations 5. Then solve for Y and ta-da you find the answer. 3x-8(5x-3)=24. 3x-40x+24=24. Hope this helped! :) 3x-40x=24-24 -37x=0 X=0 —————— Sub x=0 into (1) -5(0)+y=-3 Y=-3 .: (0,-3)

Add answer